Ethanol Extract Activity of Teak Leaves (Tectona grandis L) Against Histopotological Appearance of Pancreatic Organs in Rats (Rattus norvegicus) Model Type II DM - Nuralifah; Parawansah; Ruslin; Rachma Malina; Emma Haerunnita (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Diabetes mellitus is a disease characterized by increased blood glucose levels and changes in the histopathological structure of the islets of Langerhans of the pancreas. One of the plants used empirically as an antidiabetic is the teak plant (Tectona grandis Linn). The content compounds that are thought to act as antidiabetics are flavonoids. Purpose: The purposes of this study is to determine the activity of the ethanol extract of Tectona grandis L leaves which has antihyperglycemic activity as seen from the histopathology of the pancreas of white rats (Rattus norvegicus). Methods: Modeling diabetes mellitus in test animals was carried out by inducing 40 mg/kg BW streptozotocin intraperitoneally. There were 6 treatment groups, namely the normal control group, the positive control group, the negative control group, and the teak leaf ethanol extract group at doses of 100, 200, and 300 mg/kg. Results: The ethanol extract of Tectona grandis leaves has repair activity for regenerating endocrine cells in the islets of Langerhans with an average number of endocrine cells in the normal control group of 483 cells, positive control group 474 cells, negative control 318 cells, dose 100 mg/kg body weight 450 cells, a dose of 200 mg/KBB 462 cells and a dose of 300 mg/KBB 469 cells and it can regenerate endocrine cells. Conclusion: the ethanol extract of Tectona grandis L leaves at a dose of 300 mg/kg BW has activity in repairing endocrine cells with cell morphology almost resembling normal cells.